Blackening and odorization of urban rivers: a bio-geochemical process. Issue 3 (27th December 2017) - Liang, Zhiwei; Siegert, Michael; Fang, Wenwen; Sun, Yu; Jiang, Feng; Lu, Hui; Chen, Guang-Hao; Wang, Shanquan
Abstract: Urban rivers constitute a major part of urban drainage systems, and play critical roles in connecting other surface waters in urban areas. Black-odorous urban rivers are widely found in developing countries experiencing rapid urbanization, and the mismatch between urbanization and sewage treatment is thought to be the reason. The phenomena of blackening and odorization are likely complex bio-geochemical processes of which the microbial interactions with the environment are not fully understood. Here, we provide an overview of the major chemical compounds, such as iron and sulfur, and their bio-geochemical conversions during blackening and odorization of urban rivers. Scenarios explaining the formation of black-odorous urban rivers are proposed. Finally, we point out knowledge gaps in mechanisms and microbial ecology that need to be addressed to better understand the development of black-odorous urban rivers. Abstract : This review comprehensively summarizes the complex bio-geochemical processes in blackening and odorization of urban rivers.